2009
DOI: 10.1007/s11090-009-9177-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Chemical Reactor with Exploding Water Jet

Abstract: Exploding water jet discharge simultaneously generating powerful UV radiation, non-thermal plasma, and aerosol of fine water droplets has potential applications for removal of chemical and biological pollutants from air and water streams. A model plasma chemical reactor based on the exploding water jet discharge is considered. The radiation properties of the discharge, reactions of nitrogen oxide and hydrogen peroxide formation, and reactions of carbon dioxide and hydrogen sulfide decomposition are studied exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The lines characteristic of O 2 (oxygen atomic line-777 nm), N 2 (nitrogen atomic line, 869.4 nm), and OH radicals (309 nm) appeared only for the streamer discharge. This result indicates that OH radicals can be produced only by the streamer discharge, as suggested by earlier results (see Sun et al (1997), Šunka et al (1999), Sugimoto et al (2001, Shmelev (2008), Shmelev et al (2009), Kanazawa et al (2009Kanazawa et al ( , 2011, Dilecce and De Benedictis (2011) and Elsawah et al (2012)), but are negligible for glow corona discharge. Kanazawa et al (2009) have generated positive streamer discharges over the water surface.…”
Section: Optical Emission Spectroscopy Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…The lines characteristic of O 2 (oxygen atomic line-777 nm), N 2 (nitrogen atomic line, 869.4 nm), and OH radicals (309 nm) appeared only for the streamer discharge. This result indicates that OH radicals can be produced only by the streamer discharge, as suggested by earlier results (see Sun et al (1997), Šunka et al (1999), Sugimoto et al (2001, Shmelev (2008), Shmelev et al (2009), Kanazawa et al (2009Kanazawa et al ( , 2011, Dilecce and De Benedictis (2011) and Elsawah et al (2012)), but are negligible for glow corona discharge. Kanazawa et al (2009) have generated positive streamer discharges over the water surface.…”
Section: Optical Emission Spectroscopy Studiessupporting
confidence: 77%
“…For pulse discharges, by an average current of 1-6 mA, Shmelev et al (2008Shmelev et al ( , 2009 observed a glow discharge along a liquid jet of the length of 18 mm, the transition of this discharge to sliding surface discharge, and finally to low-current arc discharge by the current increasing to about 20 mA. The electron temperature in this discharge was estimated to be 1-2 eV, and neutral gas temperature, based on Planck distribution, to T ≈ 5000 K. The light emitted by the discharge was generated by the excited/ionised gaseous molecules, water molecules, and products of water photolysis.…”
Section: Optical Emission Spectroscopy Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma-based N 2 fixation process has already been tested in different kind of plasma reactors, for both NH 3 synthesis from H 2 and N 2 and NO x synthesis from O 2 and N 2. , The most promising results were delivered for NO x production in a microwave (MW) reactor at reduced pressure, yielding an energy cost of 0.3 MJ/mol for a NO x yield of 14% . Second place is a gliding arc (GA) reactor, with a 2% NO x yield and 2.8 MJ/mol energy consumption, reached at atmospheric pressure .…”
Section: Introductionmentioning
confidence: 99%
“…For plasma-based NO x formation, a larger number of different plasma types have been investigated, including various thermal and nonthermal discharges. Table gives a nonexhaustive overview of some characteristic results. Again, the energy consumption values reported are only for the reactors and not for the overall process, except for the Birkeland–Eyde process (first row in the table).…”
mentioning
confidence: 99%